Bazalnocelični karcinom - Zagoričnik, Blanka (Radiology and oncology (Ljubljana), 1999)
Basal cell carcinoma is the most common type of skin cancer. It usually appears on the sun-exposed skin and effects mainly people over 50 years. It grows with local infiltration and destruction of tissue, but there is a limited capacity to metastasize. On the basis of clinical findings we distinguish various types of basal cell carcinoma. Becouse of many different faces of basal cell carcinoma in different diagnosis one has to consider many other cutaneous tumors.
Keywords: Carcinoma, basal cell; Diagnosis; Diagnosis, differential; diagnostika; karcinom; kožne bolezni; rak (medicina); Skin neoplasms